2015
DOI: 10.1007/s10508-015-0588-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Facial and Body Hair Distribution in Women’s Judgments of Men’s Sexual Attractiveness

Abstract: Facial and body hair are some of the most visually conspicuous and sexually dimorphic of all men's secondary sexual traits. Both are androgen dependent, requiring the conversion of testosterone into dihydrotestosterone via the enzyme 5α reductase 2 for their expression. While previous studies on the attractiveness of facial and body hair are equivocal, none have accounted as to how natural variation in their distribution may influence male sexual attractiveness. In the present study, we quantified men's facial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 102 publications
3
33
1
Order By: Relevance
“…However, preferences for facial hair follow the opposite pattern, becoming greater when considering long‐term than short‐term relationships (Neave & Shields, ; Dixson & Brooks, ). Men's facial hair is judged as most attractive when at intermediate levels between a clean‐shaven appearance and full beardedness (Neave & Shields, ; Dixson & Brooks, ; Dixson et al ., ; Janif et al ., ; Saxton et al ., ; Dixson & Rantala, ), which coincides with the intermediate ratings of masculinity and dominance between the lowest ascribed to clean‐shaven faces and the highest ascribed to full beardedness (Neave & Shields, ; Dixson & Brooks, ). Thus, there may be a threshold of facial hair density and facial masculinity at which beards operate as an attractive trait (Neave & Shields, ; Dixson & Brooks, ).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, preferences for facial hair follow the opposite pattern, becoming greater when considering long‐term than short‐term relationships (Neave & Shields, ; Dixson & Brooks, ). Men's facial hair is judged as most attractive when at intermediate levels between a clean‐shaven appearance and full beardedness (Neave & Shields, ; Dixson & Brooks, ; Dixson et al ., ; Janif et al ., ; Saxton et al ., ; Dixson & Rantala, ), which coincides with the intermediate ratings of masculinity and dominance between the lowest ascribed to clean‐shaven faces and the highest ascribed to full beardedness (Neave & Shields, ; Dixson & Brooks, ). Thus, there may be a threshold of facial hair density and facial masculinity at which beards operate as an attractive trait (Neave & Shields, ; Dixson & Brooks, ).…”
Section: Introductionmentioning
confidence: 57%
“…Prior to providing ratings, participants were given a written instruction taken from previous studies guiding them in how to apply the six‐point Likert scales (0 = very low–10 = very high) for the rating condition to which they were assigned. The ‘attractiveness’ condition asked participants to look at each face and rate it for sexual attractiveness using the scale immediately below (Dixson & Rantala, ). The ‘short‐term attractiveness’ condition asked participants to rate the men when imagining the type of person who would be attractive in a short‐term relationship.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cultures, the presence of a beard enhances the perception of masculinity in men [19]. In some regions, such as Saudi Arabia [20], most adult males have a mustache and would prefer it to as thick as possible [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies didn't tap into features amenable to facial hair surgery: uniformity and coverage. The most recent and large-scale study on the subject did address this question, and found that in a group of 3,805 women, men with more evenly and continuously distributed facial hair were rated as more sexually attractive than men with patchier facial hair (Dixson & Rantala, 2016).…”
Section: Men's Motivationmentioning
confidence: 99%